Identifying seafarer training needs for operating future autonomous ships: a systematic literature review. Issue 2 (3rd April 2022) - Emad, Gholam Reza; Enshaei, Hossein; Ghosh, Samrat
ABSTRACT: Autonomous ships are expected to become operational in the foreseeable future. However, so far, most of the discussions have been centred on automation technology with less emphasis on training of seafarers who shall operate them. Depending on the level of autonomy, it is imperative that these ships will still be operated by humans either onshore or onboard. Thus, it is critical to identify the training needs of operators and the facilities that will be required to deliver them. This paper reviews the current state of knowledge on maritime education and training (MET) of future operators of autonomous and unmanned ships. An extensive review of the literature revealed that currently, there is an absence of a framework for training the future operators of autonomous vessels. Moreover, the exact equipment that will be needed for training is also not known. As the literature on operational requirement of autonomous ships is limited, this paper expanded the review of the literature to industries which have already embraced the autonomous systems and in particular the framework utilised for training the workforce that operates and manage those autonomous systems.